The Role of Antiepileptic Treatment in the Recurrence Rate of Seizures After First Attack: A Randomized Clinical Trial - ASSARZADEGAN, Farhad; TABESH, Hanif; HESAMI, Omid; DERAKHSHANFAR, Hojjat; BELADI MOGHADAM, Nahid; SHOGHLI, Arya; BEALE, Andrew David; HOSSEINI-ZIJOUD, Seyed-Mostafa (Iranian Journal of Child Neurology, 2015)
<!--[if gte mso 9]> 1024x768 <![endif]--> <!--[if gte mso 9]> 1024x768 <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> How to Cite This Article: Assarzadegan F, Tabesh H, Hesami O, Derakhshanfar H, Beladi Moghadam N, Shoghli A, Beale A.D, Hosseini- Zijoud S.M. The Role of Antiepileptic Treatment in the Recurrence Rate of Seizures After First Attack: A Randomized Clinical Trial. Iran J Child Neurol. Spring 2015; 9(2):46-52. Abstract Objective Epilepsy is a serious, potentially life-shortening brain disorder that occurs in patients of all ages and races. A total of 2–4% of people have experienced seizures at least once in their lifetime. Although treatment usually begins after a seizure, it is an important question whether the first cases of seizure do need to be treated by antiepileptic drugs. In this manner, we compare the recurrence rates of epilepsy in first seizure patients treated with sodium valproic acid as an antiepileptic drug versus a placebo. Material & Methods In a randomized clinical trial study, 101 first seizure patients were randomly divided into two groups: one group was treated with antiepileptic drugs (sodium valproate 200mg, three times a day) and the other group was given a placebo. The recurrence rate of seizures was evaluated and compared between the groups after 6 months of follow up. Results Eight recurrence cases were detected. All recurrence cases came from the placebo group, with four patients suffering an additional seizure after four months and between 4-6 month follow up. A comparison of recurrence rate detected a statistically significant difference between the drug group and placebo group. Conclusion Our data shows that the recurrences occurred only in the placebo group with the difference between the recurrence rates in the placebo versus drug-treated was significant. Our results suggest that drug therapy for people after their first seizure attack might reduce the probability of seizure recurrence.